PELAKSANAAN PROGRAM POSYANDU DAN PERILAKU HIDUP SEHAT IBU DAN ANAK DI DESA SIDOMULYO, KECAMATAN GODEAN KABUPATEN SLEMAN DAERAH ISTIMEWA YOGYAKARTA - Umar Nain (Jurnal Pallangga Praja (JPP), 2021)
This study aims to: (1) analyze the continuity of healthy behavior of mothers and children eventhough their involvement in Posyandu is low due to poor Posyandu services; (2) analyze the healthybehavior of mothers and children in the community which is institutionalized by the communityitself, although at the initial level it was introduced by Posyandu. This research uses a descriptivesurvei approach. The population of this research is 348 mothers who have babies and toddlers, whoare the target of the Posyandu service program. The number of samples taken was 100 respondentswith a simple random sampling technique because the population was homogeneous. Data obtainedthrough questionnaires, in-depth interviews and direct observation. Data analysis was carried outby processing descriptive statistical data. The unit of analysis is mother and child who have adyadic relationship. The results showed that the low involvement of mothers in Posyandu was not an obstacle for mothers to behave in a healthy manner on an ongoing basis. This is because inthe community there are various formal, semi-formal and village institutions that institutionalizehealthy living accompanied by the availability of service facilities outside the Posyandu that can beused by mothers to meet the needs of a healthy life. The healthy behavior of mothers and children inthe family is included in the high category seen from the frequency of mothers providing nutritiousfood for the family, maintaining food hygiene, boiling water before drinking, providing completeimmunizations to their babies. , drinking, baby clothes and utensils, conducting pregnancy checkups7-9 times during pregnancy, using modern health care facilities for childbirth, as well as activelyparticipating as an acceptor for Independent Family Planning.